The Role of Consumers in Fostering Circular Economy in Indonesia - Pratiwi, Putu Yani; Handra, Tessa; Sutisna, Felix (Journal of Accounting, Business and Management (JABM), 2024)
Consumers play an important role in transforming the economic system into a circular economy. Some literature highlighted that consumer demand has become an enabler for businesses to adopt circular practices. However, other literature argues that although consumers are aware of environmental sustainability issues, their adoption of circular products and services is still low, which is termed as an "intention–action gap." This "intention–action gap" becomes a socio-cultural barrier for businesses to adopt circular practices. This paper aims to increase knowledge and understanding about the role of consumers perceived by circular start-ups. A qualitative case study approach was employed by conducting in-depth interviews with four circular start-ups. This study is expected to shed light on the role of consumers either as enablers or barriers to the circular economy in Indonesia.